2007
DOI: 10.1088/0022-3727/40/12/022
|View full text |Cite
|
Sign up to set email alerts
|

Modification of ink-jet paper by oxygen-plasma treatment

Abstract: A study on oxygen-plasma treatment of ink-jet paper is presented. Paper was exposed to a weakly ionized, highly dissociated oxygen plasma with an electron temperature of 5 eV, a positive-ion density of 8 × 1015 m−3 and a density of neutral oxygen atoms of 5 × 1021 m−3. Optical emission spectroscopy (OES) was applied as a method for detection of the reaction products during the plasma treatment of the paper. OES spectra between 250 and 1000 nm were measured continuously during the plasma treatment. The wettabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 24 publications
3
37
1
Order By: Relevance
“…1b), a significant amount of C1 carbon was detected in the original sample, suggesting that cellulose surface did not consist of pure cellulose. Results for O/C atomic ratio are in compliance with previous studies (Topalovic et al 2007) because even in ''pure'' cellulose material still exists a spectral intensity of C1 carbon component, contributing typically with 10-20% of intensity of C 1s XPS (Mitchell et al 2005) and indicating hydrocarbon contamination or some modification of polymer (Vesel et al 2007(Vesel et al , 2010. It was also reported recently that it was difficult to completely remove waxes containing carbon C1 and therefore it could be taken as a marker for the presence of such substances (Fras et al 2005), which the authors are prone to believe is the case in this work, given the industrial pretreatments carried out to the fabrics.…”
Section: Wetting Propertiessupporting
confidence: 86%
“…1b), a significant amount of C1 carbon was detected in the original sample, suggesting that cellulose surface did not consist of pure cellulose. Results for O/C atomic ratio are in compliance with previous studies (Topalovic et al 2007) because even in ''pure'' cellulose material still exists a spectral intensity of C1 carbon component, contributing typically with 10-20% of intensity of C 1s XPS (Mitchell et al 2005) and indicating hydrocarbon contamination or some modification of polymer (Vesel et al 2007(Vesel et al , 2010. It was also reported recently that it was difficult to completely remove waxes containing carbon C1 and therefore it could be taken as a marker for the presence of such substances (Fras et al 2005), which the authors are prone to believe is the case in this work, given the industrial pretreatments carried out to the fabrics.…”
Section: Wetting Propertiessupporting
confidence: 86%
“…A huge flux of chemically reactive neutral oxygen atoms allows for excellent chemical reactivity of oxygen plasma, [6] while the low kinetic temperature of neutral gas assures for minimisation of thermal loads. [7] Such plasma is therefore suitable for modification of surface properties without any damage to the bulk properties of solid materials. [7] Particularly interesting is modification of organic materials by oxygen plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Such plasma is therefore suitable for modification of surface properties without any damage to the bulk properties of solid materials. [7] Particularly interesting is modification of organic materials by oxygen plasma. Popular technologies based on interaction of oxygen plasma with organic materials include modification of the surface properties of polymer materials [8 -12] especially for improved adhesion of various coatings, [13 -15] selective plasma etching of polymer composites, [16 -18] and plasma sterilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous molecules partially ionize, dissociate and excite in a gaseous discharge forming reactive particles which readily interact with polymer surface causing modification of surface properties. Numerous authors reported excellent results on improved hydrophylicity for several types of polymers [5] including polyethersulphone [6][7], polyphenylene sulphide [8], polystyrene [9][10], polyvinylchloride [11][12][13], polyethylene naphthalate [14], polymethyl methacrylate [15], cellulose [16][17][18][19]. The authors report a different behavior of polymers upon plasma treatment.…”
Section: Introductionmentioning
confidence: 99%